Long-term outcome of surgical cryoablation for refractory ventricular tachycardia in patients with non-ischemic cardiomyopathy. Issue 3 (10th April 2017) - Liang, Jackson J; Betensky, Brian P; Muser, Daniele; Zado, Erica S; Anter, Elad; Desai, Nimesh D; Callans, David J; Deo, Rajat; Frankel, David S; Hutchinson, Mathew D; Lin, David; Riley, Michael P; et al.
Abstract: Aims: Limited data exist on the long-term outcome of patients (pts) with non-ischemic cardiomyopathy (NICM) and ventricular tachycardia (VT) refractory to conventional therapies undergoing surgical ablation (SA). We aimed to investigate the long-term survival and VT recurrence in NICM pts with VT refractory to radiofrequency catheter ablation (RFCA) who underwent SA. Methods and results: Consecutive pts with NICM and VT refractory to RFCA who underwent SA were included. VT substrate was characterized in the electrophysiology lab and targeted by RFCA. During SA, previous RFCA lesions/scars were identified and targeted with cryoablation (CA; 3 min/lesion; target −150 °C). Follow-up comprised office visits, ICD interrogations and the social security death index. Twenty consecutive patients with NICM who underwent SA (age 53 ± 16 years, 18 males, LVEF 41 ± 20%; dilated CM = 9, arrhythmogenic right ventricular CM = 3, hypertrophic CM = 2, valvular CM = 4, and mixed CM = 2) were studied. Percutaneous mapping/ablation in the electrophysiology lab was performed in 18 and 2 pts had primary SA. During surgery, 4.9 ± 4.0 CA lesions/pt were delivered to the endocardium (2) and epicardium (11) or both (7). VT-free survival was 72.5% at 1 year and over 43 ± 31 months (mos) (range 1–83mos), there was only one arrhythmia-related death. There was a significant reduction in ICD shocks in the 3-mos preceding SA vs. the entire follow-up period (6.6 ± 4.9 vs. 2.3 ± 4.3 shocks/pt, P = 0.001). Conclusion: In select pts with NICM and VT refractory to RFCA, SA guided by pre-operative electrophysiological mapping and ablation may be a therapeutic option.